2020
DOI: 10.1002/acr.24066
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Medicines Partnership: Organizational Structure and Preliminary Data From the Phase 1 Studies of Lupus Nephritis

Abstract: The Accelerating Medicines Partnership (AMP) Lupus Network was established as a partnership between the National Institutes of Health, pharmaceutical companies, nonprofit stakeholders, and lupus investigators across multiple academic centers to apply high‐throughput technologies to the analysis of renal tissue, urine, and blood from patients with lupus nephritis (LN). The AMP network provides publicly accessible data to the community with the goal of generating new scientific hypotheses and improving diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…In this study, we present extensive transcriptional and clonotypic changes in lupus-prone mice, which may serve as a resource for ongoing profiling of SLE (165,166). Characterization of novel myeloid subsets, CD8 metabolism, and MZ B cell loss highlights disease mechanisms for potential therapeutic targeting.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we present extensive transcriptional and clonotypic changes in lupus-prone mice, which may serve as a resource for ongoing profiling of SLE (165,166). Characterization of novel myeloid subsets, CD8 metabolism, and MZ B cell loss highlights disease mechanisms for potential therapeutic targeting.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the commonality of immune marker gene expression and their potential utility in other glomerular diseases, we evaluated their expression in the immune single cell data from the lupus nephritis subjects in the Accelerating Medicines Partnership (AMP), 21 as reported by Arazi et al 22 We observed that the top 16 immune marker genes from FSGS monocytes and lymphocytes were also highly expressed in the monocyte and lymphocyte clusters, respectively from lupus nephritis subjects (Figures 6A-B). We also evaluated the expression of these immune genes in the bulk RNA-seq data of urine samples from another multi-ethnic cohort of lupus nephritis subjects and found that subjects with active disease (defined as urine protein: creatinine ratio > 0.5) had higher expression of these genes than those with inactive disease (urine protein: creatinine ratio ≤ 0.5), reflecting the higher presence of monocytes/lymphocytes in the urine of subjects with active lupus nephritis (Figure 6G).…”
Section: Immune Signatures In Lupus Nephritismentioning
confidence: 99%
“…77 Recent initiatives of industry-academia collaborations, such as the Innovative Medicines Initiative in Europe ($5B), the Accelerating Medicines Partnership in the U.S. ($215M), and the Precision Medicine Initiative in China ($9.2B), are parts of larger strategies with expected long-term benefits. [78][79][80] These initiatives invest in basic science and biomedical research capabilities in universities. India could leverage its strength in pharmaceuticals and information technology by undertaking a similar initiative.…”
Section: Pillar 2: Precision Medicinementioning
confidence: 99%